Marketing Strategy in Increasing Sales Apeng Cashew Trading Business Central Buton District - Katjina, Husna; Suriadi, Suriadi (Institute for Research and Community Service, 2023)
The aim of the study was to find out how the marketing strategy was in increasing sales of Apeng Cashew Cashew Trading Business (UD) in Lombe, Gu District, Central Buton Regency. The method used is observation and interviews. The method of data analysis is descriptive qualitative. Based on the results of research and discussion it can be concluded that the marketing strategy of UD. Cashew Cashew Apeng in Lombe Gu District Central Buton Regency which consists of product, price, place, promotion, people, process and physical evidence can increase sales in 2021 Rp. 128,500,000, - increasing in 2022 by Rp. 173,300,000,-. The suggestions given are (1) So that UD. Apeng cashew nuts in Lombe, Gu sub-district, Central Buton regency, in the promotion strategy can use brochures that can provide information about cashew products and use signboards at cashew processing and selling places so that the sales obtained can continue to increase. (2) So that future researchers can add research variables so that they can enrich research results.